Molecular interaction of tea catechin with bovine β-lactoglobulin: A spectroscopic and in silico studies - Nasser Abdulatif Al-Shabib; Javed Masood Khan; Ajamaluddin Malik; Md. Tabish Rehman; Mohamed F. AlAjmi; Fohad Mabood Husain; Malik Hisamuddin; Nojood Altwaijry (Elsevier, 2020)
Polyphenols has attained pronounced attention due to their beneficial values of health and found to prevent several chronic diseases. Here, we elucidated binding mechanism between frequently consumed polyphenol "tea catechin" and milk protein bovine beta-lactoglobulin (β-Lg). We investigated the conformational changes of β-Lg due to interaction with catechin using spectroscopic and in silico studies. Fluorescence quenching data (Stern-Volmer quenching constant) revealed that β-Lg interacted with catechin via dynamic quenching. Thermodynamic data revealed that the interaction between β-Lg and catechin is endothermic and spontaneously interacted mainly through hydrophobic interactions. The UV-Vis absorption and far-UV circular dichroism (CD) spectroscopy exhibited that the tertiary as well as secondary structure of β-Lg distorted after interaction with catechin. Molecular docking and simulation studies also confirm that catechin binds at the central cavity of β-Lg with high affinity (~105 M−1) and hydrophobic interactions play significant role in the formation of a stable β-Lg-catechin complex. Keywords: Polyphenol, Catechin, Beta-Lactoglobulin, Protein and proteinligand, interaction